EFEKTIVITAS METODE DEMONTRASI TERHADAP KETERAMPILAN SISWA DALAM PERAWATAN JENAZAH KELAS XII DI SMK AL FUTUH TIKUNG LAMONGAN - Hasyim; Hidayatul Fitriyah (CENDEKIA, 2020)
This research is motivated by the low learning outcomes of students in the use of learning methods. The purpose of this study was to determine the effectiveness of demonstration methods on students' skills in caring for the XII class of SMK Al Futuh Tikung. This research uses quantitative research methods, the research design is Quasi Experimental Type Nonequivalent Control Group Design, the research design has a control group and an experimental group. Based on the results of the study showed that "The effectiveness of the demonstration method on students' skills in caring for the corpse. class XII SMK Al Futuh Tikun ”, this can be proven from the sig. (2-tailed) of 0.004 <0.05 and the average learning outcome before using the demonstration method (pre test) was 70.6 and increased after using the demonstration method (post test) to 87.86